2021
DOI: 10.1002/minf.202100113
|View full text |Cite
|
Sign up to set email alerts
|

ADMET Predictability at Boehringer Ingelheim: State‐of‐the‐Art, and Do Bigger Datasets or Algorithms Make a Difference?

Abstract: Computational methods assisting drug discovery and development are routine in the pharmaceutical industry. Digital recording of ADMET assays has provided a rich source of data for development of predictive models. Despite the accumulation of data and the public availability of advanced modeling algorithms, the utility of prediction in ADMET research is not clear. Here, we present a critical evaluation of the relationships between data volume, modeling algorithm, chemical representation and grouping, and tempor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(45 citation statements)
references
References 48 publications
1
35
0
Order By: Relevance
“…For example, a recent review from Boehringer Ingelheim reported SVM and RF as the top performers on internal ADMET (absorption, distribution, metabolism, excretion, and toxicity) prediction tasks, and furthermore presented mixed results regarding the benefit of increasing training set sizes, with 8 out of 23 datasets recording negative effects on the predictive performance when using more data 13 . The debate of whether more data is helpful for virtual screening, usually framed in the context of virtual docking, has still not been settled 14 .…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent review from Boehringer Ingelheim reported SVM and RF as the top performers on internal ADMET (absorption, distribution, metabolism, excretion, and toxicity) prediction tasks, and furthermore presented mixed results regarding the benefit of increasing training set sizes, with 8 out of 23 datasets recording negative effects on the predictive performance when using more data 13 . The debate of whether more data is helpful for virtual screening, usually framed in the context of virtual docking, has still not been settled 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Most production models are for absorption, distribution, metabolism, excretion, and toxicity (ADMET) end points because those are of interest to many therapeutic areas, and large numbers of diverse molecules (i.e., from many chemical classes) are assayed. For recent examples from other companies see Aleksić et al, Goller et al, and Cumming et al Merck & Co., Inc., Kenilworth, NJ, United States, has maintained multiple generations of infrastructure to generate and update QSAR models since 2005, most recently using QSAR Workbench as the platform. There is a Web-based interface on which chemists can sketch molecules and get predictions, but predictions may also be made on other platforms.…”
mentioning
confidence: 99%
“…Nowadays, it is recognized that there are QSAR methods that give a slightly higher average predictivity. In practice, though, RF is still competitive because prediction accuracy for most data sets seems to be limited more by the data than the QSAR methodology. , In any case, our historical predictions are made with RF, so that is what we will examine here.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Typically a large number of diverse molecules are assayed for those end points. Aleksić et al and Goller et al discuss recent examples from pharma. Our company has been maintaining ADMET models since 2005 …”
mentioning
confidence: 99%